Rejuvenating The Shunned Art of Diagnostic Nasal Endoscopy Using Angled Endoscopes- A Descriptive Study: Life Sciences-Health - Datt Mehta, Shashwat; P, Karthikeyan; S, Vijayasundaram (International Journal of Life Science and Pharma Research, 2022)
Nasal endoscopy is a minimally invasive, routine outpatient diagnostic procedure. With 0 degree scope being used as the first and often only endoscope in diagnostic nasal endoscopy, this study will explicate use of angled scopes to identify anatomical variants and common disease pointers. A Cross-sectional descriptive study involving 756 subjects, between age group of 12-80 years with chronic nasal complaints. All subjects underwent diagnostic nasal endoscopy with 0-, 30- & 70-degree endoscopes. Common anatomical variants along with disease markers were identified. Anatomical variants embedded in lateral wall of nose such as accessory maxillary ostium (AMO) & medialized uncinated (MU), were seen better on 30 & 70 degree scopes (AMO -12% & 12.8% respectively & MU -7.6 and 8.1% of study population respectively), when compared to 0 degree scopes (AMO-5.6% & MU-7 %). Disease pointers projected a general trend of being better visualized on angled scopes of 30 & 70 degree endoscopes. It included discharging meati (27.9 % & 26.3% subjects on 30 & 70 degree vs 25 % subjects on 0 degree), polyposis (20.2 & 19.6% on 30 & 70 degree vs 13% on 0), eschar (6.1% & 5.7% on 30 & 70 degree vs 4.5% on 0), CSF rhinorrhoea (1.3% & 2.1% on 30 & 70degree vs 0.5% on 0). With inclusion of angled scopes in routine nasal endoscopies, one gains capability to diagnose early disease processes, mucosal changes and learn intra nasal anatomy better. The angulation of lenses provides a better field of vision with appropriate magnification and illumination.